1998
DOI: 10.2105/ajph.88.5.759
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and daily mortality in Sydney, Australia, 1989 through 1993.

Abstract: OBJECTIVES: This study examined the effects of outdoor air pollutants in Sydney, Australia, on daily mortality. METHODS: Time-series analysis was performed on counts of daily mortality and major outdoor air pollutants (particulates, ozone, and nitrogen dioxide) in Sydney (1989 to 1993) with adjustment for seasonal and cyclical factors. Poisson regression was calculated with allowance for overdispersion and autocorrelation. The effects of lagging exposure by 0 to 2 days were assessed with single- and multiple-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Hence respiratory health effects on people can be observed when they are exposed at elevated concentrations. Studies indicated that an increase in daily mean PM 10 concentrations might cause an increase in daily mortality and hospital admissions (Schwartz, 1991;Dockery and Pope, 1994;Morgan et al, 1998aMorgan et al, , 1998b. With significant relevance to human health, understanding the behavior of PM 10 is crucial for important administrative and industrial decision making in a metropolitan area.…”
Section: Introductionmentioning
confidence: 99%
“…Hence respiratory health effects on people can be observed when they are exposed at elevated concentrations. Studies indicated that an increase in daily mean PM 10 concentrations might cause an increase in daily mortality and hospital admissions (Schwartz, 1991;Dockery and Pope, 1994;Morgan et al, 1998aMorgan et al, , 1998b. With significant relevance to human health, understanding the behavior of PM 10 is crucial for important administrative and industrial decision making in a metropolitan area.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that NO2 is acting wholly or partly as a Colvile et al, 2000. The transport sector as a polluter 6 surrogate for another pollutant that has similar properties and source distribution (Poloniecki et al (1997), , Morgan et al (1998)). However, others have shown an effect of NO2 after allowing for the effects of other pollutants (Castellsagué et al (1995), Pantazopoulou et al (1995), Linn et al (1996)).…”
mentioning
confidence: 99%
“…Morgan et al (1998) showed that excess deaths were significantly associated with NO 2, PM 10 and NO 2 after adjusting for weather confounders in full season in Sydney. However, in our study, other pollutants (e.g.…”
Section: Discussionmentioning
confidence: 98%